SIKLUS PDCA DAN FILOSOFI KAIZEN - FITRIANI Fitriani (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstract: TQM's success in developing a company's quality is needed. One way to develop quality is to make continuous improvement. There are several approaches that an institution can take to make continuous improvements, including the plan-do-study / check-act (PDSA / PDCA) cycle and philosophy kaizen. Kata Kunci: PDCA Kaizen